SHARIA BANKS AND THEIR BUSINESS EARNINGS: AN EMPIRICAL EXPLORATORY OF THE CASE OF INDONESIA - Ahmad Abbas; Wa Ode Rayyani; Rini Purnamasari (Airlangga International Journal of Islamic Economics and Finance, 2020)
This research aims to identify the tendency of business earnings obtained by shariah banks and detect its patterns. The sample of this research was sharia commercial banks listed in Indonesia Bank and Financial Services Authority over the period of 2010-2017. The data of financial statements were utilized in this research. The result of this research pointed out that net income during eight periods of observation has shown fluctuative result. The further result found that the value of smoothness tends to go zero. It indicated that earnings pattern in sharia banks is highly smooth.